Carcinoembryonic antigen cell adhesion molecule 1 inhibits the antitumor effect of neutrophils in tongue squamous cell carcinoma. Issue 2 (12th January 2019) - Wang, Ning; Wang, Qingjie; Chi, Jinghua; Xiang, Fenggang; Lin, Mei; Wang, Wenhong; Wei, Fengcai; Feng, Yuanyong
Abstract : Carcinoembryonic antigen cell adhesion molecule 1 (CEACAM1), a transmembrane glycoprotein, has multiple functions. In tongue squamous cell carcinoma (TSCC), CEACAM1 overexpression is correlated with neutrophil infiltration, and both are associated with poor clinical outcomes. However, the mechanism underlying CEACAM1's effect on neutrophil function in TSCC remains unclear. We cocultured tongue carcinoma cells overexpressing CEACAM1‐4L, CEACAM1‐4S and differentiated HL‐60 cells. This significantly upregulated the expression of MMP‐9, interleukin 8, and VEGF‐A in the differentiated HL‐60 cells and downregulated the expression of TNF‐α, relative to vector and blank control groups ( P  <   0.05). Additionally, CEACAM1 overexpression in tongue carcinoma cells weakened the cytotoxicity of differentiated HL‐60 cells in the coculture system ( P  <   0.05). Thus, CEACAM1 expression in TSCC may induce an antitumor to protumor transformation of neutrophils. We performed qRT‐PCR and ELISA to evaluate the underlying mechanism, and found that CEACAM1 expression in tongue carcinoma cells upregulated transforming growth factor β1 (TGF‐β1) expression, while blocking of TGF‐β1 inhibited the neutrophils' changes in the coculture system. Immunohistochemical analysis of clinical specimens revealed strong expression of TGF‐β1 protein in TSCC. TGF‐β1 expression was positively correlated with CEACAM1 expression, lymph node metastasis, and tumor recurrence. Double immunofluorescence results revealed colocalization of CEACAM1 and TGF‐β1 protein in TSCC. A xenograft nude mouse model revealed that CEACAM1 overexpression in TSCC promoted tumor formation and growth, and was associated with more neutrophils infiltration. Our results indicate that CEACAM1 overexpression in TSCC may induce transformation of neutrophils from antitumor to protumor type via TGF‐β1, which may further promote tumor progression. Abstract : Overexpression of CEACAM1 in tongue carcinoma cells lead to upregulation of IL‐8, VEGF‐A, MMP‐9 but downregulation of TNF‐α in differentiated HL‐60, and a blocking antibody to TGF‐β1 inhibited the changes of differentiated HL‐60 cells in the coculture system.